Faktor Penghambat Kesetaraan Hak Politik Perempuan Kuwait Pasca Amandemen Undang-Undang Nomor 35 Tahun 1962 - Randhi Satria; Septyanto Galan Prakoso; Iim Fathimah Timorria; Nadia Dian Ardita (Universitas Diponegoro, 2019)
Kuwait is one of the countries in the Middle East which considered as a moderate of Muslim majority state. The amendment of Election Law No. 35 Year 1962 in 2005, which granted women’s rights to vote and run for office, gives a way for women to be able to get more roles in Kuwait’s parliament. However, the implementation of this law takes four years of waiting for Kuwaiti women to get the representation in Kuwait’s legislative assembly. On the national elections in 2008, Kuwaiti women were unable to get the seat. This article argues that the main impediment for women’s inability to win any seat in 11th and 12th Assemblies is caused by the failure of Kuwaiti women to cooperate and support each other. This article aims to examine the Kuwaiti women’s struggle for political rights along with the condition of Kuwaiti’s social norms which affect women’s roles. Using women empowerment theory and the explanation of Kuwait’s socio-political condition, this article also try to predict the future of women representation in Kuwaiti’s political life.